PENERAPAN STRATEGI POLITIK DALAM PENINGKATAN PARTISIPASI PEMILIH PEREMPUAN PADA PILKADA SERENTAK DI KOTA MAGELANG - Wibowo, Eko Ari; Muradi, Muradi; Sudirman, Arfin (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
Women voters became one of the strategic voter segments in the political dissemination carried out by the Magelang City KPU because in addition to the population that exceeded male voters, it was also due to obstacles for women in terms of education, economy and social causes which made women more in the domestic area and limited access to information including electoral issues. In the implementation of simultaneous regional elections in 2015, the KPU set a target of national voter participation rate of 77.5%. As an effort to reach the target, Magelang City KPU implemented a strategy in carrying out political socialization to women voters. Qualitative methods are used in this study, and data collection techniques are used through interviews and documentation. Determination of informants is done with the purpose of using the snowball strategy. The results and discussion revealed that the Magelang City Election Commission applied an offensive and defensive strategy simultaneously but with different target groups of women voters.